Maternal serum human chorionic gonadotropin and pregnancy-associated plasma protein-A in pregnancies with fetal homozygous α-thalassemia-1 disease - Tongprasert F. (2014)
Objective: To compare the levels of maternal serum free β-hCG and PAPP-A between pregnancies with fetal homozygous α-thalassemia-1 disease and unaffected pregnancies. Materials and Methods: One hundred and forty eight pregnancies at risk for fetal homozygous α-thalassemia-1 disease scheduled for cordocentesis at 18 to 22 weeks were recruited into the study. Maternal serum free β-hCG and PAPP-A concentrations were measured before cordocentesis, and the final fetal diagnosis of homozygous α-thalassemia-1 disease was based on fetal Hb typing using high-performance liquid chromatography. Results: Maternal serum concentration of free β-hCG was significantly higher in women with fetal homozygous α-thalassemia-1 disease than those with unaffected fetuses (P = 0.018), whereas the concentrations of PAPP-A was not significantly different (P = 0.184). The median MoM of free β-hCG in the affected group was 1.38 MoM and in the unaffected group was 0.88 MoM (P = 0.020). Conclusion: At midpregnancy, maternal serum free β-hCG levels are significantly higher in pregnancies with fetal homozygous α-thalassemia-1 disease, signifying that the disease could be a confounder for interpretation free β-hCG level in Down syndrome screening program. Nevertheless PAPP-A level seems to be similar in both groups. © 2012 John Wiley & Sons, Ltd.